Safety of the novel vector vaccine against Brucella abortus based on recombinant influenza viruses expressing Brucella L7/L12 and OMP16 proteins, in cattle - Kaissar Tabynov; Zhailaubay Kydyrbayev; Sholpan Ryskeldinova; Bolat Yespembetov; Nazym Syrymkyzy; Indira Akzhunusova; Abylai Sansyzbay (Journal of Vaccines and Immunology - Peertechz Publications, 2015)
This paper presents the results of a study of the safety of new vector vaccine against B. abortus based on recombinant influenza A subtype H5N1 or H1N1 (viral constructs vaccine formulation) viruses expressing Brucella ribosomal protein L7/L12 and Omp16,in cattle. To increase the effectiveness of the vaccine, adjuvants such as Montanide Gel01 or chitosan were included in its composition. Immunization of cattle (5 animals per group) with the viral constructs vaccine formulation only, or its combination with adjuvants Montanide Gel01 or chitosan, were conducted via the conjunctival method using cross prime (influenza virus subtype H5N1) and booster (influenza virus subtype H1N1) vaccination schedules. Vaccine candidates were evaluated in comparison with the positive (B. abortus S19) and negative (PBS) controls. Comprehensive studies involving thermometry and clinical examination, hematology and biochemical blood analysis, showed that all of the viral constructs vaccine formulation, as well as their combination with adjuvants, compared to the commercial bacterial vaccine B. abortus S19 were completely safe in cattle. Furthermore it is shown that the developed vaccines can effectively differentiate vaccinated animals from infected animals.